Phosphatase inhibition by sodium orthovanadate displays anti-inflammatory action by suppressing AKT-IKKβ signaling in RAW264.7 cells - Han Gyung Kim; Seong-Gu Jeong; Ji Hye Kim; Jae Youl Cho (Toxicology Reports, 2022)
Sodium orthovanadate (Na3VO4) is an inhibitor of phosphatases that acts as a phosphate analog and is being developed as an anti-diabetes drug. Phosphatases play important roles in inflammatory signal pathways by modulating the removal of phosphate moieties of key signaling proteins. However, the role of protein phosphatases on the inflammatory response has not been fully established. In this study, we investigated how phosphatases can control the inflammatory response using Na3VO4 in LPS-stimulated RAW264.7 cells and explored the molecular mechanisms by NO assay, mRNA analysis, immunoblotting analysis, kinase assay, luciferase reporter gene assay, and mutation strategy. Na3VO4 decreased the release of nitric oxide (NO) and suppressed the expression of pro-inflammatory genes at the transcriptional level, without cytotoxicity. The translocation of nuclear factor (NF)-κB subunits into the nucleus and the level of p-IκBα were reduced by Na3VO4, as was IKKβ activity. Na3VO4 inhibited NF-κB-Luc activity under AKT1/2 and IKKβ overexpression. However, the inhibitory effect of Na3VO4 against NF-κB-Luc was not observed in the group overexpressing both AKT2 and IKKβ-M10, a mutant in which the 10 serine residues in the autophosphorylated region of the C-terminal were replaced with alanine. Na3VO4 directly decreased the activity of protein phosphatase 1α (PP1α) and protein phosphatase 2 A (PP2A) by 95%. Phosphatase inhibition by Na3VO4 also selectively suppressed AKT-IKKβ signaling by directly blocking the phosphatase activity of PP1 and PP2A, consequently down-regulating NF-κB and inflammatory gene expression. Therefore, these results suggest that vanadium compounds including Na3VO4 can be developed as anti-inflammatory drugs.